Does Competitiveness Count? The Role of Competitive Attitudes in Health Risk and Preventive Health Behaviours - Keresztes, Noémi; Pikó, Bettina; Fülöp, Márta (European Journal of Mental Health, 2015)
Adolescents’ health behaviours are influenced by many social variables. Among these factors, competitiveness may also have an important role. However, the relationship between competitiveness and health behaviours is a less investigated field of research. Our data were collected in 2005, in the Southern Plain region of Hungary. 548 questionnaires were analysed (age range: 14 to 21 years; M = 16.3 years; SD = 1.3 years; response rate: 91.3%; 42% female). Self-administered questionnaires were used for data collection. Our findings pointed out that competitiveness was in significant relationship with both health risk and preventive health behaviours as previous studies had suggested. We identified three independent dimensions of competitiveness using factor analysis, namely: ‘Enjoyment of competition’; ‘Avoidance of social conflict’, and ‘Fear of competition’. These factors were found to have different roles in varying health behaviours. In contrast with previous studies, we pointed out that health risk behaviours were more frequent among respondents characterised by ‘Avoidance of social conflict’ and ‘Fear of competition’. In terms of preventive health behaviours, we pointed out that physical activity was in significant relationship with every competitiveness dimension. On the other hand, diet control and oral hygiene were associated only with the ‘Avoidance of social conflict’ and ‘Fear of competition’ factors. Based on these results we may conclude that students with a tendency towards social conflict avoidance and fear of competition would be an important target group for health promotion programs.